Can we fight drugs using communication campaigns? A framed field experiment - Marcela Ibanez; Juanita Vasquez (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
This paper uses a framed field experiment to test the effect of persuasive communication as a strategy in the fight against drugs in Colombia. Our design varies the salience and the degree of informativeness of the messages that participants receive, while highlighting particular negative effects of growing coca in the community. We find that messages that make the relation of coca cultivation with violence salient are the most effective at reducing coca investments. Our results suggest that the main mechanism at play is attitudinal change rather than a change in beliefs. Interestingly, we find that exposure to persuasive messages translates into lower intentions to cultivate coca in the future. We conclude that interventions that aim at increasing 'awareness' of the negative effects that coca has in the community are a promising policy instrument in the fight against drugs.
Keywords: A13; G11; D03; D83; K42; Z13; 330; field experiment; attitudinal change; communication campaigns; illegal behavior